Zambia : Financial Sector Assessment Program-Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses the findings of the assessment of the financial system in Zambia. Nonperforming loans have risen and private sector credit growth has turned negative, owing to the severe pressures of 2015-16. The pressures included slower economic growth, sharply lower copper prices, electricity shortages, very tight monetary policy, and mounting fiscal arrears and severe fiscal funding pressures. Looking ahead, the financial system faces considerable risks, owing to high dependence on copper exports, rising public debt and funding pressures, and an uncertain monetary policy regime. A sharper-than-expected global slowdown may lead to copper price declines and additional pressures on government finance and the exchange rate. A lack of fiscal adjustment may worsen government payments arrears, further impacting asset quality.